In vitro propagation of bamboo species through axillary shoot proliferation: a review - Sandhu, Manpreet (2017)
Bamboos, very relevant plants in many countries around the world, are propagated at large scale with extreme difficulties. Use of seeds is challenging because of plant’s sporadic flowering and long flowering cycles, together with seed recalcitrance and consumption by wild animals. Vegetative propagation of bamboo is mainly conducted by cuttings and by air layering. However, these methods are only useful at small-scale because they damage the mother plants, propagation material is bulky and difficult to be transported and is only available during few months of the year. Therefore, in vitro propagation offers the opportunity to obtain large progenies from elite genotypes. In most cases, when developing protocols for in vitro propagation of plants, specific conditions for individual species, genotypes and even development stages of the donor plants must be identified by trial-and-error experiments. Because of the size of and the large diversity observed in this plant family, it usually takes several months to define most adequate culture medium, combination of plant growth regulators and of other compounds for fostering the desired development in the explants. Therefore, in this detailed review, that also puts together results from hard-to-find literature, we list all identified cases, in which development of axillary shoots was used to propagate bamboo plants, by presenting successful ways for disinfection, in vitro bud sprouting, multiplication, rooting and acclimatization.